Image quality assessment of fast fourier transform domain watermarked images - Olanrewaju, Rashidah Funke; Aburas, A. A.; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha (2009)
Digital watermarking is the processing of embedding digital signature into the host media such as image, video, text, audio etc. During the watermarking process, images are subjected to variety of attacks such as noise in transmission channel, geometric attacks,compression, processing like filtering, etc, all this affect the visual quality of watermarked image. Thus, there is a need for image quality assessment of watermarked images in relation to the original images. Several measures of image metrics are available in the field of image processing however they are application based. This paper discusses watermarking in FFT domain and some of the image quality metric that can be applied. Experiments are conducted using the Full Reference (FR) images. We used Mean Square Error (MSE), Root Mean Square (RMS), Structural Similarity (SSIM), Image Fidelity Measure (IFM), Correlation Coefficient Index (CCI) and Peak Signal to Noise Ratio (PSNR) as our quality assessment. Result shows that CCI, SSIM, and IFM are most appropriate for measuring quality of watermarking system.